Retinal Oxygen Metabolism and Haemodynamics in Patients With Multiple Sclerosis and History of Optic Neuritis - Kallab, Martin; Hommer, Nikolaus; Schlatter, Andreas; Bsteh, Gabriel; Altmann, Patrick; Popa-Cherecheanu, Alina; Pfister, Martin; Werkmeister, René M.; Schmidl, Doreen; Schmetterer, Leopold; Garhöfer, Gerhard (Frontiers in Neuroscience, 2021)
Vascular changes and alterations of oxygen metabolism are suggested to be implicated in multiple sclerosis (MS) pathogenesis and progression. Recently developed in vivo retinal fundus imaging technologies provide now an opportunity to non-invasively assess metabolic changes in the neural retina. This study was performed to assess retinal oxygen metabolism, peripapillary capillary density (CD), large vessel density (LVD), retinal nerve fiber layer thickness (RNFLT) and ganglion cell inner plexiform layer thickness (GCIPLT) in patients with diagnosed relapsing multiple sclerosis (RMS) and history of unilateral optic neuritis (ON). 16 RMS patients and 18 healthy controls (HC) were included in this study. Retinal oxygen extraction was modelled using O2 saturations and Doppler optical coherence tomography (DOCT) derived retinal blood flow (RBF) data. CD and LVD were assessed using optical coherence tomography (OCT) angiography. RNFLT and GCIPLT were measured using structural OCT. Measurements were performed in eyes with (MS+ON) and without (MS-ON) history for ON in RMS patients and in one eye in HC. Total oxygen extraction was lowest in MS+ON (1.8±0.2µl O2/min), higher in MS-ON (2.1±0.5µl O2/min, p=0.019 vs.MS+ON) and highest in HC eyes (2.3±0.6µl O2/min, p=0.002 vs. MS, ANOVA p=0.031). RBF was lower in MS+ON (33.2±6.0µl/min) compared to MS-ON (38.3±4.6µl/min, p=0.005 vs. MS+ON) and HC eyes (37.2±4.7µl/min, p=0.014 vs. MS+ON, ANOVA p=0.010). CD, LVD, RNFLT and GCIPL were significantly lower in MS+ON eyes. The present data suggest that structural alterations in the retina of RMS patients are accompanied by changes in oxygen metabolism, which are more pronounced in MS+ON than in MS-ON eyes. Whether these alterations promote MS onset and progression or occur as consequence of disease warrants further investigation.